Mouse models of advanced spontaneous metastasis for experimental therapeutics - Francia, Giulio (Nat Rev Cancer, 2011)
An enduring problem in cancer research is the failure to reproduce highly encouraging preclinical therapeutic findings using transplanted or spontaneous primary tumours in mice in clinical trials of patients with advanced metastatic disease. There are several reasons for this, including the failure to model established, visceral metastatic disease. We therefore developed various models of aggressive multi-organ spontaneous metastasis after surgical resection of orthotopically transplanted human tumour xenografts. In this Opinion article we provide a personal perspective summarizing the prospect of their increased clinical relevance. This includes the reduced efficacy of certain targeted anticancer drugs, the late emergence of spontaneous brain metastases and the clinical trial results evaluating a highly effective therapeutic strategy previously tested using such models.